Membrane Inlet Mass Spectrometry at the Crossroads of Photosynthesis, Biofuel, and Climate Research. Issue 2 (21st April 2020) - Burlacot, Adrien; Li-Beisson, Yonghua; Peltier, Gilles
Abstract : Advances in algal biology have built on gas exchange measurements by MIMS in the fields of photosynthesis, biofuel production, and climate research.